Identification of potential drug targets for varicose veins: a Mendelian randomization analysis - Lin, Jianfeng; Zhou, Jiawei; Liu, Zhili; Zeng, Rong; Wang, Lei; Li, Fangda; Cui, Liqiang; Zheng, Yuehong (Frontiers in Cardiovascular Medicine, 2023)
Introduction Increasing evidence suggested that plasma proteins were related to the onset or severity of varicose veins. However, the causal association between the two had yet to be demonstrated. Methods To identify potential drug targets for varicose veins of lower extremities, we undertook a comprehensive screen of plasma protein with two-sample Mendelian Randomization (MR) method. We used recently-reported cis-variants as genetic instruments of 2,004 plasma proteins, then applied MR to a recent meta-analysis of genome-wide association study on varicose veins (22,037 cases and 437,665 controls). Further, pleiotropy detection, reverse causality testing, colocalization analysis, and replication were utilized to strengthen the causal effects of prioritized proteins. Phenome-wide MR (PheW-MR) of prioritized proteins for risk of 525 diseases was conducted to screen potential side-effect profiles. Results We identified eight plasma proteins significantly associated with risk of varicose veins after Bonferroni correction (P<2.495×10-5), with five being protective (LUM, POSTN, RPN1, RSPO3 and VAT1) and three harmful (COLEC11, IRF3, SARS2). Most identified proteins showed no pleiotropic effects except for COLLEC11. Bidirectional MR and MR Steiger testing excluded reverse causal relationship between varicose veins and prioritized proteins. Colocalization analysis indicated that COLEC11, IRF3, LUM, POSTN, RSPO3, SARS2 shared the same causal variant with varicose veins. Finally, seven identified proteins replicated with alternative instruments except for VAT1. Further PheW-MR revealed that only IRF3 had potential harmful adverse side effects. Conclusions We identified eight potential causal proteins for varicose veins with MR. A comprehensive analysis indicated that IRF3, LUM, POSTN, RSPO3 and SARS2 might be potential drug targets for varicose veins.